Character Building for Gen Z: Interconnection of Existential Humanistic Approaches Based on the Qur’an in Counseling Guidance - Arienza, Della Nur; Zahro, Indah Fajrotuz (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
Abstrak: This study aims to discuss the humaniastic existential approach based on the Qur’an in Islamic guide and counseling to shape and strengthen the character of gen Z. the research conducted in writing this article uses the library research method, the research process is carried out by collecting various literature data collection an information related to the theme taken in this study. Document used as sources of research data using several scientific literature in the form of books, journals and supporting websites. The concept of interconnection of the humanistic existential approach based on the Qur’an is a combination of general knowledge and religious knowledge. In the humanistic existential concept, humans are considered unique with their respective potentials that can be developed and are positive and also dynamic or always moving towards goodness and humans have full rights to determine their own action and destiny. While Islam sees that humans are more inclined to be religious and monotheistic (recognizing themselves as servants of Allah) who are given the task of Allah as the Caliph on earth who are given various potentials such as faith, reason, feelings, senses and are given freedom of will.